Injury risk factors and their priority for mitigation in women`s netball: a systematic review and Delphi consensus - Whitehead, S.; Mackay, L.; Jones, B.; Heyward, O.; Fox, A. S.; Chesson, L. J.; Scantlebury, S.; Janse van Rensburg, D. C. (British Journal of Sports Medicine, 2025)
This study aimed to establish consensus on injury risk factors in netball via a combined systematic review and Delphi method approach. A systematic search of databases (PubMed, Scopus, MEDLINE, SPORTDiscus and CINAHL) was conducted from inception until June 2023. Twenty-four risk factors were extracted from 17 studies and combined with a three-round Delphi approach to achieve consensus. In round one, experts listed perceived risk factors for injury in netball which were combined with the risk factors identified via the systematic review. In round two and round three, experts rated their level of agreement with each risk factor on a 5-point Likert scale (1, strongly disagree to 5, strongly agree). Consensus was defined as =80% agreement (with<10% in disagreement). In round three, experts also rated the priority for mitigating the risk factor (1, very low to 5, very high). Nineteen experts participated in round one and round two, and 16 participated in round three (response rate 84%). One-hundred and nine risk factors for injury were identified by the systematic review and experts combined. Sixty-one risk factors reached consensus, categorised into five groups: `individual characteristics` (n=22), `lifestyle` (n=11), `training and competition` (n=14), `sport science and medical provision` (n=6) and `facilities and equipment` (n=8). `Poor landing technique/mechanics` had a median (IQR) mitigation priority rating of 5 (1), while all others had median ratings of 3-4.5. This study identifies a range of risk factors for injury, provides focus areas for injury prevention and highlights the importance of a multidisciplinary approach to injury mitigation in netball.